Gasifier cookstove technology for households and artisanal processing - CGIAR Research Program on Rice (2019)
Components of the technology were fabricated, tested and validated in Benin. Piloting was carried out in Benin, Cote d’Ivoire, Niger, Nigeria and Togo. Standardization was done with private companies in Benin, Cameroon, Cote d’Ivoire, Mali, Nigeria and Senegal. Technical drawings of the equipment were prepared and made publicly available.